mutator nuclear gene inducing a wide spectrum of cytoplasmically inherited chlorophyll deficiencies in barley - Prina, A.R (Theoretical and applied genetics, 1992)
Some striped plants were observed in plots of a long-grain mutant barley grown at a field nursery. All of the plants of these plots, which were naturally self pollinated, were individually harvested, and most of their progenies (92.5%) segregated seedlings carrying chlorophyll deficiencies (CD) as determined by greenhouse analysis. The majority of the mutant seedlings (84.3%) showed a pattern of longitudinal chlorophyll sectors. The spectrum of CD was wide among the solid mutant seedlings and consisted of three main types (albina, viridis and discontinuous). In association with some CD types morphological changes were frequently observed. Non-CD-associated morphological changes and diminished seed-set were scarce and, so far, none of them has proved to be inherited. Analysis of CD in reciprocal crosses and backcrosses proved that while CD were transmitted cytoplasmically their induction was controlled by a single nuclear mutator gene, active when homozygous. In addition once the CD were induced, they were expressed independently of the nuclear constitution. The results suggest that the mutator gene induces diverse mutational events on chloroplast (cp) DNA. In barley, as in other monocots, nuclear genes which are inductors of cytoplasmic genetic changes have been reported. However, all of them produced a narrower spectrum of CD and had a more rapid sorting-out of the cytoplasmic mutants than what we observed. On this basis a distinction between chloroplast and mitochondrial (mt) mutator genes is proposed. Accordingly, the chloroplast mutator here described would be the first one reported for monocots. Increased knowledge on this subject can play a fundamental role in elucidating organelle heredity and its interactions with the nuclear genome. Moreover, this material could be a valuable source of variability of the otherwise conservative genetic information encoded in the chloroplast.